Work values for generations Y and Z stricto sensu accounting students - Sousa, Rayane Camila da Silva; Colauto, Romualdo Douglas (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
The study analyzes the values of work interpreted as significant for students from generations Y and Z of stricto sensu in accounting. The study included 337 stricto sensu graduate students in the Accounting area, 246 from Generation Y and 91 from Generation Z. The study uses the Revised Scale of Work-Related Values, Descriptive Analysis and Exploratory Factor Analysis. The work values considered most important were those on job stability and financial independence that made up the Safety factor; the least important values were those related to status, sovereignty and prestige that made up the Power factor. The findings help managers to understand the characteristics of the new generations and makes it possible to academics to rethink educational practices.